Special issue: “Darkness matters” - Andersen, Camilla Eline; Guttorm, Hanna Ellen; Koro-Ljungberg, Mirka; Löytönen, Teija; Osgood, Jayne; Otterstad, Ann Merete; Rantala, Teija; Rautio, Pauliina; Välimäki, Anita (Reconceptualizing Educational Research Methodology, 2017)